Flower, Metaphor, and Portugalidade: António de Sousa de Macedo and Mariana de Luna’s Complementary Use of Flores - Wade, Jonathan (Revista de Escritoras Ibéricas, 2020)
ABSTRACT: António de Sousa de Macedo’s Flores de España, Excelencias de Portugal (1631) and Mariana de Luna’s Ramalhete de flores (1642) both make use of a central floral metaphor to exalt their native Portugal. Luna’s modest bouquet and Sousa de Macedo’s meticulous arrangement are introduced to the reader through two sonnets by Soror Violante do Céu. Whereas Luna writes to the newly crowned king João IV in celebration of the Restauração (1640), Sousa de Macedo’s is a non-native reader who he would convince of Portuguese preeminence. While they differ in context and scale, both works employ the language of portugalidade to achieve their respective ends. RESUMEN: Tanto Flores de España, Excelencias de Portugal (1631) de António de Sousa de Macedo como Ramalhete de flores (1642) de Mariana de Luna emplean las flores como metáfora nuclear para exaltar su Portugal natal. El ramillete modesto de Luna y el arreglo minucioso de Sousa de Macedo se presentan al lector a través de dos sonetos de Sor Violante do Céu. Mientras que Luna le escribe al recién coronado rey João IV en celebración de la Restauração (1640), el destinatario de Sousa de Macedo es un lector extranjero a quien pretende convencer de la preeminencia portuguesa. Aunque difieren en contexto y extensión, las dos obras emplean la lengua de portugalidade para lograr sus respectivos propósitos.